EFISIENSI PENGGUNAAN AIR BERSIH DENGAN MEMANFAATKAN KEMBALI AIR LIMBAH MEMGGUNAKAN TEKNOLOGI INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) AEROB - ANAEROB BIOFILTER - Wayan Hari Premananda; Dewa Jati Primajana (Yayasan Nusantara Hasana Berdikari, 2023)
The existence of health facilities in the form of hospitals can improve the health standard of the people of Denpasar, as evidenced by the high life expectancy in 2022 equal to 75.3 years. By increasing the level of public health, other sectors will receive a positive influence, especially the economic sector. The high need for health facilities in the city of Denpasar has caused many investors to start pursuing the health business, especially hospitals. Businesses in the Health sector provide considerable profits with a relatively high Initial Rate of Return (IRR) or investment return rate of 50.44% (Arwati, 2016). In addition to providing benefits to the community and businesses, the health business, in the form of hospitals, also has a significant negative impact on the environment. The characteristics of the waste generated by hospital operations are in the form of domestic waste and B3 waste (hazardous toxic materials) such as leftover syringes, leftover laboratory washing water and leftover reagents. The management of the resulting liquid B3 waste can be carried out with the operation of an WWTP (wastewater treatment installation). It is necessary to carry out calculations related to the performance efficiency of the WWTP so as to ensure that the processed water is suitable for reuse and to calculate the clean water savings that can be achieved in order to apply the concept of a sustainable economy. Based on the research results, the level of treatment efficiency which is quite high, which is more than 90%, will produce processed water that can be reused to support operational activities. The use of ground water for operational activities can be reduced by 60% or around 48 m3/day.